2021
DOI: 10.1177/03010066211029218
|View full text |Cite
|
Sign up to set email alerts
|

Professional Versus Self-Applied Makeup: Do Makeup Artists Add Value?

Abstract: While a number of studies have investigated the effects of makeup on how people are perceived, the vast majority have used professionally applied makeup. Here, we tested the hypothesis that professional makeup is more effective than self-applied makeup. We photographed the same target women under controlled conditions wearing no makeup, makeup they applied themselves, and makeup applied by professional makeup artists. Participants rated the faces as appearing more attractive, more feminine, and as having highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…In a series of two experiments, participants rated faces wearing makeup as more attractive than faces without makeup. Our results offer further corroboration of previous findings, which suggest that makeup increases perceived facial attractiveness [ 9 18 ]. The most important finding of our study was that faces with makeup elicited more negative EPN and more positive LPP amplitudes than did faces without makeup in both Experiment 1 and Experiment 2.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In a series of two experiments, participants rated faces wearing makeup as more attractive than faces without makeup. Our results offer further corroboration of previous findings, which suggest that makeup increases perceived facial attractiveness [ 9 18 ]. The most important finding of our study was that faces with makeup elicited more negative EPN and more positive LPP amplitudes than did faces without makeup in both Experiment 1 and Experiment 2.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, Experiment 2 replicated the effects of makeup that were observed for one’s own face on the EPN and LPP amplitudes in Experiment 1 and extended these effects to other female faces. These findings are consistent with the findings of existing research that has demonstrated that facial makeup improves the perceived attractiveness of both an individual’s own face and others’ faces [ 9 18 ].…”
Section: Methodssupporting
confidence: 92%
See 3 more Smart Citations